Impact of Work Environment and Job Satisfaction on Quality of Work Life (QWL) on Private School Teachers in Tokha Municipality, Nepal - Nischal Risal,; Dhruba Lal Pandey,; Dikshya Bhujel, (Interdisciplinary Journal of Management and Social Sciences, 2025)
The existing literature has provided unanimous results on work environment, job satisfaction and quality of work life on employees in the academic domain. Thus, the study aims to determine the effect of the work environment and job satisfaction on the quality of work life of private school teachers in Tokha, Kathmandu, Nepal. Need satisfaction theory aims to provide actionable insights for improving the quality of work life. The descriptive and causal research designs have been adopted. The data is collected from 109 respondents from the Tokha area using the purposive sampling method. The sample has been drawn based on the participation of teachers in the survey. The study found a significant positive relationship between work environment, job satisfaction, and quality of work life. By aligning the work environment and satisfaction styles or levels, organizations can foster a positive workplace and culture, improve relation rates, and ultimately thrive in the present era. Enhancing working conditions and strengthening training programs, providing a concise overview of the findings and implications for improving teachers' quality of work life. The study findings emphasized practical implication to stakeholders by improving working conditions and professional development. So, investing in the quality of work life for teachers is a strategic imperative that enhances both the well-being of educators and the educational outcomes for students, underscoring the importance of addressing the quality of work life.